Oligomeric ricinoleic acid preparation promoted by an efficient and recoverable Brønsted acidic ionic liquid - You, Fei; He, Xing; Gao, Song; Li, Hong-Ru; He, Liang-Nian (Beilstein Journal of Organic Chemistry, 2020)
Raw material from biomass and green preparation processes are the two key features for the development of green products. As a bio-lubricant in metalworking fluids, estolides of ricinoleic acid are considered as the promising substitute to mineral oil with a favorable viscosity and viscosity index. Thus, an efficient and sustainable synthesis protocol is urgently needed to make the product really green. In this work, an environment-friendly Brønsted acidic ionic liquid (IL) 1-butanesulfonic acid diazabicyclo[5.4.0]undec-7-ene dihydrogen phosphate ([HSO3-BDBU]H2PO4) was developed as the efficient catalyst for the production of oligomeric ricinoleic acid from ricinoleic acid under solvent-free conditions. The reaction parameters containing reaction temperature, vacuum degree, amount of catalyst and reaction time were optimized and it was found that the reaction under the conditions of 190 °C and 50 kPa with 15 wt % of the [HSO3-BDBU]H2PO4 related to ricinoleic acid can afford a qualified product with an acid value of 51 mg KOH/g (which corresponds to the oligomerization degree of 4) after 6 h. Furthermore, the acid value of the product can be adjusted by regulating the reaction time, implying this protocol can serve as a versatile method to prepare the products with different oligomerization degree and different applications. The other merit of this protocol is the facile product separation by stratification and decantation ascribed to the immiscibility of the product and catalyst at room temperature. It is also worth mentioning that the IL catalyst can be used at least for five cycles with high catalytic activity. As a result, the protocol based on the IL catalyst, i.e. [HSO3-BDBU]H2PO4 shows great potential in industrial production of oligomeric ricinoleic acid from ricinoleic acid.
Keywords: bio-lubricant; ionic liquids; oligomeric ricinoleic acid; ricinoleic acid; sustainable catalysis

(untitled) - Ebata, H.; Yasuda, M.; Toshima, K.; Matsumura, S. (J. Oleo Sci., 2008)

(untitled) - Alonso, D. M.; Bond, J. Q.; Dumesic, J. A. (Green Chem., 2010)

(untitled) - Biermann, U.; Bornscheuer, U.; Meier, M. A. R.; Metzger, J. O.; Schäfer, H. J. (Angew. Chem., Int. Ed., 2011)

(untitled) - Meier, M. A. R.; Metzger, J. O.; Schubert, U. S. (Chem. Soc. Rev., 2007)

(untitled) - Miao, S.; Wang, P.; Su, Z.; Zhang, S. (Acta Biomater., 2014)

(untitled) - Biermann, U.; Friedt, W.; Lang, S.; Lühs, W.; Machmüller, G.; Metzger, J. O.; Rüsch gen. Klaas, M.; Schäfer, H. J.; Schneider, M. P. (Angew. Chem., Int. Ed., 2000)

(untitled) - Nayak, P. L. (J. Macromol. Sci., Rev. Macromol. Chem. Phys., 2000)

(untitled) - Thomas, A.; Matthäus, B.; Fiebig, H.-J. (Ullmann's Encycl. Ind. Chem., 2000)

(untitled) - Scarpa, A.; Guerci, A. (J. Ethnopharmacol., 1982)

(untitled) - Mutlu, H.; Meier, M. A. R. (Eur. J. Lipid Sci. Technol., 2010)

(untitled) - Ogunniyi, D. S. (Bioresour. Technol., 2006)

(untitled) - Van der Steen, M.; Stevens, C. V. (ChemSusChem, 2009)

(untitled) - Goodrum, J. W.; Geller, D. P. (Bioresour. Technol., 2005)

(untitled) - Kim, H. T.; Baritugo, K.-A.; Oh, Y. H.; Hyun, S. M.; Khang, T. U.; Kang, K. H.; Jung, S. H.; Song, B. K.; Park, K.; Kim, I.-K.; Lee, M. O.; Kam, Y.; et al. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Borsotti, G.; Guglielmetti, G.; Spera, S.; Battistel, E. (Tetrahedron, 2001)

(untitled) - Yoshida, Y.; Kawase, M.; Yamaguchi, C.; Yamane, T. (J. Am. Oil Chem. Soc., 1997)

(untitled) - Hayes, D. G.; Kleiman, R. (J. Am. Oil Chem. Soc., 1995)

(untitled) - Zerkowski, J. A. (Lipid Technol., 2008)

(untitled) - Vadgama, R. N.; Odaneth, A. A.; Lali, A. M. (Heliyon, 2019)

(untitled) - Bódalo-Santoyo, A.; Bastida-Rodríguez, J.; Máximo-Martín, M. F.; Montiel-Morte, M. C.; Murcia-Almagro, M. D. (Biochem. Eng. J., 2005)

(untitled) - Bódalo, A.; Bastida, J.; Máximo, M. F.; Montiel, M. C.; Gómez, M.; Murcia, M. D. (Biochem. Eng. J., 2008)

(untitled) - Bódalo, A.; Bastida, J.; Máximo, M. F.; Montiel, M. C.; Murcia, M. D.; Ortega, S. (Biochem. Eng. J., 2009)

(untitled) - Horchani, H.; Bouaziz, A.; Gargouri, Y.; Sayari, A. (J. Mol. Catal. B: Enzym., 2012)

(untitled) - Yoshida, Y.; Kawase, M.; Yamaguchi, C.; Yamane, T. (J. Jpn. Oil Chem. Soc., 1995)

(untitled) - Erhan, S. M.; Kleiman, R.; Isbell, T. A. (J. Am. Oil Chem. Soc., 1993)

(untitled) - Zhang, Q.; Zhang, S.; Deng, Y. (Green Chem., 2011)

(untitled) - Petkovic, M.; Seddon, K. R.; Rebelo, L. P. N.; Silva Pereira, C. (Chem. Soc. Rev., 2011)

(untitled) - Wang, G.; Sun, S. (J. Oleo Sci., 2017)

(untitled) - Li, M.; Wu, F.; Gu, Y. (Chin. J. Catal., 2019)

(untitled) - El‐Harairy, A.; Yiliqi; Lai, B.; Vaccaro, L.; Li, M.; Gu, Y. (Adv. Synth. Catal., 2019)

(untitled) - El‐Harairy, A.; Yiliqi; Yue, M.; Fan, W.; Popowycz, F.; Queneau, Y.; Li, M.; Gu, Y. (ChemCatChem, 2019)

Chin Patent - Ye, F.; He, L. N.; You, F.; Li, H. R.; Wang, Q. R.; Gao, S.; He, X.; Cui, X. Y. (A protocol for oligomeric ricinoleic acid preparation and in-situ separation, 2020)

ASTM D664-17 (ASTM International, 2017)